Digital Literacies or Digital Competence: Conceptualizations in Nordic Curricula - Godhe, Anna-Lena (2019)
This article examines how the concepts of digital literacies and digital competence are conceptualized in curricula for compulsory education within the Nordic countries. In 2006, the European Union defined digital competence as one of eight key competences for lifelong learning. The terms digital literacies and digital competence have since been used interchangeably, particularly in policy documents concerning education and the digitalization of educational systems and teaching. However, whether these concepts carry similar meanings, and are understood in a similar way, across languages and cultures is not self-evident. By taking the curricula in Sweden, Denmark, Finland, and Norway as examples, this article attempts to clarify similarities and differences in how the concepts are interpreted, as well as what implications this has for the digitalization of education. The analyses reveal that different terms are used in the curricula in the different countries, which are connected to themes or interdisciplinary issues to be incorporated into school subjects. The conceptualizations of the terms share a common emphasis on societal issues and a critical approach, highlighting a particular Nordic interpretation of digital literacies and digital competence.